Primary Prevention of Cardiovascular Disease in Asia: Challenges - Dalakoti, Mayank; Lin, Norman H.Y.; Yap, Jonathan; Cader, Aaysha; Dipanker, Prajapati; Lee, Derek; Raja Shariff, Raja Ezman; Cuenza, Lucky; Honda, Satoshi; Malis, Vorn; Jiang, Haowen; Hirachan, Anish; et al. (JACC. Advances (Online), 2025)
Asia is home to 60% of the world's population, including the world's 2 most populous countries, India (1.1B) and China (1.2B). With cardiovascular disease burden and mortality increasing, the role of preventive cardiology is increasingly important. The challenges in addressing the cardiovascular disease burden in Asia include unique cardiometabolic features of the different populations, heterogeneity of risk factors among Asian countries, differing levels of health literacy and socioeconomic status, suboptimal infrastructure to support preventive care especially in the primary care sector, high out-of-pocket costs, and environmental pollution. Asia is a large continent that comprises diverse populations with varying cultures, socioeconomic status, and health literacy levels. Effective preventive cardiology may require differential health care resource allocation and financing models. [Display omitted] •The vast social, cultural, and economic potential of people in Asia is threatened by a rising cardiovascular disease burden, with enhanced primary prevention a key solution.•Challenges include unique cardiometabolic features, issues arising from health literacy and socioeconomic disadvantage, infrastructure and environment.•Despite the significant heterogeneity within Asia, shared challenges toward improved CVD primary prevention call for collaborative solutions with local execution.